2010
DOI: 10.1037/a0018460
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the theatrical experience: Results from an empirical investigation.

Abstract: The article aims at explaining visitors' overall judgment of a theatrical event. A questionnaire was constructed including the 4 dimensions of the theatrical experience identified by Eversmann (2004): perceptual, cognitive, emotional, and communicative. The authors investigated 125 visitors of a production in a German community theater and confirmed that both the emotional and cognitive dimensions were determinants of visitors' overall judgment of a theatrical event. Implications for further research on the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 18 publications
3
25
0
1
Order By: Relevance
“…Collective engagement, however, was comparatively a weaker predictor of overall evaluation among the four components. Boerner et al (2010) reported similar findings that the communicative component of Eversmann's framework was not a significant driver of overall evaluation of a performance. Also similar to our results, they found that the cognitive component and the emotional component, which could be considered parallel constructs to AAEI's knowledge and authenticity components, were predictive of overall enjoyment.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Collective engagement, however, was comparatively a weaker predictor of overall evaluation among the four components. Boerner et al (2010) reported similar findings that the communicative component of Eversmann's framework was not a significant driver of overall evaluation of a performance. Also similar to our results, they found that the cognitive component and the emotional component, which could be considered parallel constructs to AAEI's knowledge and authenticity components, were predictive of overall enjoyment.…”
Section: Discussionsupporting
confidence: 69%
“…Our work is among the early attempts to validate the factor structure of performing arts experiences. Boerner et al (2010) developed items based on Eversmann's framework to examine whether the four components of perceptual, emotional, cognitive, and communicative experiences could be confirmed empirically. Their limited sample size did not allow them to conduct a CFA to evaluate the four-factor structure fully; instead, they tested each component separately and reported that each component was unidimensional.…”
Section: Discussionmentioning
confidence: 99%
“…We are less interested in the rather heterogeneous collection of higher level constructs, such as Boerner and colleagues [10] [11], Vladica and Davis [71] and Brown and Novak [12] have proposed. Instead we analyse questions separately and we use advanced cluster analysis, Multi Dimensional Scaling [77], with an adapted variation of the concept of homogeneity (Kline,[35: page 12]): "The average correlation among items".…”
Section: Quantitative Audience Evaluations Of Mediated Performancesmentioning
confidence: 99%
“…without a live audience. She uses a modified version of Boerner, Jobst and Wiemann's [10] [11] Likert scale questionnaire, resulting in scoring on three factors: emotional, cognitive and communicative responses. The quantitative results were complemented with quotes from a focus group.…”
Section: Quantitative Audience Evaluations Of Mediated Performancesmentioning
confidence: 99%
“…Damit bleibt das Zusammenspiel zwischen Kern-und Zusatzleistungen (Frage 1) ungeklärt. In der theaterwissenschaftlichen Rezeptionsforschung besteht Einigkeit darüber, dass die emotionale und die kognitive Reaktion des Zuschauers eine Rolle spielen -sowohl für die Beurteilung einer Aufführung (Cronkhite et al 1971;Tan/Schoenmakers 1984) als auch für die Beurteilung eines Theaterbesuches (Boerner et al 2010;. Konzeptionelle Modelle berücksichtigen neben der Reaktion des Zuschauers verschiedene andere Determinanten, wurden bislang jedoch nicht empirisch untersucht.…”
unclassified